2010
DOI: 10.1021/ja106506k
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Rotational Motions of Nano-objects in Engineered Environments and Live Cells with Gold Nanorods and Differential Interference Contrast Microscopy

Abstract: Gold nanorods are excellent orientation probes due to their anisotropic optical properties. Their dynamic rotational motion in the 3D space can be disclosed with Nomarski-type differential interference contrast (DIC) microscopy. We demonstrate that by using the combination of gold nanorod probes and DIC microscopy, we are able to resolve rotational motions of nano-cargos transported by motor proteins at video rate not only on engineered surfaces but also on cytoskeleton tracks in live cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
234
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(244 citation statements)
references
References 39 publications
4
234
1
Order By: Relevance
“…The cpp was necessary to allow cell penetration and consequent investigation of the possible intracellular function of these peptides. Moreover, the cpp used herein has been extensively described to transport its cargo into the cells (37,38).…”
Section: Resultsmentioning
confidence: 99%
“…The cpp was necessary to allow cell penetration and consequent investigation of the possible intracellular function of these peptides. Moreover, the cpp used herein has been extensively described to transport its cargo into the cells (37,38).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we introduced the single particle orientation and rotational tracking (SPORT) technique [34][35][36] to follow the rotational motion of plasmonic gold nanorods 37 under a differential interference contrast (DIC) microscope. Working in the principle of interferometry 38 , a DIC microscope generates disproportionate bright and dark interference patterns for gold nanorods in different orientations.…”
mentioning
confidence: 99%
“…By measuring the bright and dark DIC intensities of the gold nanorod continuously, it becomes possible to dynamically track the nanorod's orientation and rotational patterns. Using the SPORT technique with an electron-multiplying charge-coupled device running at a temporal resolution of 30 ms, we observed that a cargo tends to keep the same orientation relative to the microtubule tracks during the active transport in living cells 34 .…”
mentioning
confidence: 99%
“…This is in good agreement with the polarizationdependent rotation behaviors of plasmonic nanoparticles that have been extensively investigated in gold nanorods and nanowires. 18,39 In view of the periodic changes, a correlation between the bright and dark intensity traces is observed: the bright and dark intensities increase and decrease in the same direction. This orientation/polarization dependence is the foundation for the use of Au/Ag/SiO 2 −NRs as SPORT probes.…”
Section: * S Supporting Informationmentioning
confidence: 92%
“…18,38 Herein, the DIC contrast of an immobilized, randomly oriented Au/Ag/SiO 2 −NR is plotted as a function of excitation wavelength ( Figure S3 in the Supporting Information). The highest DIC contrast for this particle was found when a 585 ± 29 nm filter was used for illumination, which corresponds to the longitudinal dipolar plasmonic band.…”
Section: * S Supporting Informationmentioning
confidence: 99%